USING ONLINE RESOURCES FOR ENGLISH LESSONS - Barno Abdullaeva, Khujaev Alijon, Muminov Komil, Soliev Ilkhom, Yakhyaev Sobir, Gulnoza Sobirova (International Journal of Advanced Science and Technology, 2020)
As we know, nowadays digital technologies as are requirement of modern society. With their help, you can turn every lesson into an unforgettable journey and interesting research. Of course, using the Internet is fraught with many dangers. Therefore, it is important to follow the rules for using online resources. And, the teacher during the preparation for the lesson should carefully study this resource. In this article we described the efficiency of using online resources for English lessons.